2022
DOI: 10.3390/biomedicines10123230
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Oxytocin Modulates Decision-Making Depending on Outcome Predictability—A Randomized Within-Subject Controlled Trial in Healthy Males

Abstract: Oxytocin (OT) has been extensively studied with regard to its socio-cognitive and -behavioral effects. Its potential as a therapeutic agent is being discussed for a range of neuropsychiatric conditions. However, there is limited evidence of its effects on non-social cognition in general and decision-making in particular, despite the importance of these functions in neuropsychiatry. Using a crossover/within-subject, blinded, randomized design, we investigated for the first time if intranasal OT (24 IU) affects … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…In this study (Bozorgmehr et al, 2019), intranasal OT administration increased participants’ net earnings compared to control groups who received placebo or no treatments. In contrast, another study (Zebhauser et al, 2022) found that compared to control and placebo conditions, subjects given OT showed increased risk taking in the IGT. As these two studies employed nearly identical methods (same dose, route of administration, and general subject characteristics), the reason for their opposite outcomes is not clear, although it might be attributable to the use of a between-subjects (Bozorgmehr et al, 2019) vs. a within-subjects (Zebhauser et al, 2022) design.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…In this study (Bozorgmehr et al, 2019), intranasal OT administration increased participants’ net earnings compared to control groups who received placebo or no treatments. In contrast, another study (Zebhauser et al, 2022) found that compared to control and placebo conditions, subjects given OT showed increased risk taking in the IGT. As these two studies employed nearly identical methods (same dose, route of administration, and general subject characteristics), the reason for their opposite outcomes is not clear, although it might be attributable to the use of a between-subjects (Bozorgmehr et al, 2019) vs. a within-subjects (Zebhauser et al, 2022) design.…”
Section: Introductionmentioning
confidence: 87%
“…In contrast, another study (Zebhauser et al, 2022) found that compared to control and placebo conditions, subjects given OT showed increased risk taking in the IGT. As these two studies employed nearly identical methods (same dose, route of administration, and general subject characteristics), the reason for their opposite outcomes is not clear, although it might be attributable to the use of a between-subjects (Bozorgmehr et al, 2019) vs. a within-subjects (Zebhauser et al, 2022) design. Another study assessed performance in patients with bulimia and healthy controls in the Balloon Analogue Risk Task, in which subjects pump up a virtual balloon to maximize earnings, without pumping so much as to pop the balloon (which results in loss of earnings).…”
Section: Introductionmentioning
confidence: 87%
“…3.2.1. Oxytocin administration76.92% of the included studies used 24 IU intranasally administered oxytocin[27,28,30,31,51,52,[71][72][73][74], whereas two studies used higher doses of intranasal oxytocin (36 IU[24], 40 IU[71]). …”
mentioning
confidence: 99%
“…All studies employed a consistent dose regardless of participant body weight. Notably, the dose-to-task interval varied from 15 minutes to 90 minutes (15 minutes[72], 30 minutes[31], 45 minutes (15 minutes:[28,30,51,52,65,73,75], 50 minutes[27], 75 minutes[74], 90 minutes…”
mentioning
confidence: 99%